A comparison of three frameworks for measuring knowledge for teaching mathematics - Kaarstein, Hege (NOMAD Nordic Studies in Mathematics Education, 2014)
This paper presents a comparison of three different frameworks used in research projects aimed at measuring knowledge for teaching mathematics. As the included cases all build on Shulman’s theoretical framework for teacher knowledge, in which the categories subject matter content knowledge (CK) and pedagogical content knowledge (PCK) are central, his framework was used as a reference. To enable comparison across the frameworks, each framework’s categories were analysed and organized taxonomically. The results indicate agreement on a superordinate level. However, important differences were found in the operationalisation of the basic level categories mathematics CK and mathematics PCK. As the basic level normally represents clear communication of categories, this paper suggests that more attention to the operationalisation of basic level categories is needed.